2010
DOI: 10.2353/ajpath.2010.090667
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific β-Catenin Knockout Mice Exhibit Defective Bile Acid and Cholesterol Homeostasis and Increased Susceptibility to Diet-Induced Steatohepatitis

Abstract: Although the role of Wnt/beta-catenin signaling in liver growth and development is well established, its contribution in non-neoplastic hepatic pathologies has not been investigated. Here, we examine the role of beta-catenin in a murine model of diet-induced liver injury. Mice with hepatocyte-specific beta-catenin deletion (KO) and littermate controls were fed the steatogenic methionine and choline-deficient (MCD) diet or the corresponding control diet for 2 weeks and characterized for histological, biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 29 publications
9
104
1
2
Order By: Relevance
“…Choline is an essential nutrient required for efficient phosphatidylcholine synthesis necessary for the packaging and export of VLDL particles to extrahepatic organs. Feeding mice a CD diet results in hepatic steatosis with predominant TG content and unchanged cholesterol levels compared to chow-fed mice (Fig 1A), consistent with previous reports [10,20,21]. In contrast, increased hepatic cholesterol levels but unchanged TG content are observed in mice fed the HC diet ( Fig 1B).…”
Section: Resultssupporting
confidence: 81%
“…Choline is an essential nutrient required for efficient phosphatidylcholine synthesis necessary for the packaging and export of VLDL particles to extrahepatic organs. Feeding mice a CD diet results in hepatic steatosis with predominant TG content and unchanged cholesterol levels compared to chow-fed mice (Fig 1A), consistent with previous reports [10,20,21]. In contrast, increased hepatic cholesterol levels but unchanged TG content are observed in mice fed the HC diet ( Fig 1B).…”
Section: Resultssupporting
confidence: 81%
“…However, none of the diets changed the total cholesterol content at any of the time points examined (Fig. 2C), in agreement with previous findings (6,28,29). These biochemical characteristics were consistent with the staining of liver samples with oil red and filipin, which monitor the level of neutral lipids and free cholesterol, respectively (Fig.…”
Section: Mice Fed MCD and Md Diets But Not Cd Diet Exhibitsupporting
confidence: 92%
“…In a mouse model of high-fat diet-induced obesity, the Wnt/β-catenin signaling pathway was demonstrated to regulate hepatic metabolism (3). In contrast, in another study, liver-specific β-catenin knockout mice revealed increased susceptibility to methionine-and cholinedeficient diet-induced steatohepatitis (4). These reports suggest that this pathway plays an important role in hepatic metabolism.…”
Section: Introductionmentioning
confidence: 73%